2012
DOI: 10.1039/c2dt30464c
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, spectroscopic analysis and photolabilization of water-soluble ruthenium(iii)–nitrosyl complexes

Abstract: In this paper, the synthesis, structural and spectroscopic characterization of a series of new Ru(III)-nitrosyls of {RuNO}(6) type with the coligand TPA (tris(2-pyridylmethyl)amine) are presented. The complex [Ru(TPA)Cl(2)(NO)]ClO(4) (2) was prepared from the Ru(III) precursor [Ru(TPA)Cl(2)]ClO(4) (1) by simple reaction with NO gas. This led to the surprising displacement of one of the pyridine (py) arms of TPA by NO (instead of the substitution of a chloride anion by NO), as confirmed by X-ray crystallography… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
39
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 105 publications
4
39
0
1
Order By: Relevance
“…[105]. Lehnert and co-workers also point out that water may be an important player in the photochemistry [105].…”
Section: Electronic Spectroscopy and Photochemistrymentioning
confidence: 96%
See 3 more Smart Citations
“…[105]. Lehnert and co-workers also point out that water may be an important player in the photochemistry [105].…”
Section: Electronic Spectroscopy and Photochemistrymentioning
confidence: 96%
“…[105]. Lehnert and co-workers also point out that water may be an important player in the photochemistry [105]. The fact that in general UV light (<400 nm) is required for photoactivation is a disadvantage, but for topical applications this is not a limitation [40], and to overcome it, Ford [39,180] devised several strategies.…”
Section: Electronic Spectroscopy and Photochemistrymentioning
confidence: 96%
See 2 more Smart Citations
“…Merkle et al recently reported that strong π-back bonding causes a distinct lowering of the NO stretching frequency in Ru(II)NO + complexes bearing tris(2-pyridylmethyl)amine as an ancillary ligand. 59 On the basis of all the calculated results, the electronic structure of the Ru 2 (NO) 2 moiety in the closed-shell singlet state of C can be described as structure IV, [Ru(II)(NO + )] 2 , in Chart 1.…”
Section: Geometric and Electronic Structures Of Dinitrosylmentioning
confidence: 99%